Lulo (Solanum quitoense [Lamarck.]) as new landscape crop in the Mexican agro-ecosystem - Gómez-Merino, Fernando C.; Trejo-Téllez, Libia I.; García-Albarado, J. Cruz; Cadeña-Íñiguez, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
Lulo (Solanum quitoense [Lamarck.]) is a white nightshade that produces a result of exquisite taste and innovative nutraceutical properties that make it a species of great potential for its establishment and exploitation in Mexico. This species is native to the Andean region of Colombia, Ecuador and Peru, countries that concentrate its production and use. Due to various constraints, technical, commercial and organizational, the production of this crop do not supply the regional market in South American countries, and in turn, in other countries such as United States import of this white nightshade has increased, opening an important window of possibility for countries such as Mexico to develop its own technology to improve the production and productivity of this fruit for domestic consumption and export. This review discusses general aspects of the species, including the main botanical descriptors, genetic resources, improved materials, as well as environmental and agronomic requirements for their sustainable production. Suggesting some strategies for the implementation of innovations in the value chain such as guidelines for its use in Mexico as well. It is concluded that lulo is a species with potential and, it is necessary to develop research in different aspects, to provide the necessary elements that would allow the enrichment of the Mexican countryside, in terms of both environmental services such as agronomic and aggregation of value.
Keywords: agro-ecosystems; naranjilla; nutraceutical fruits; solanaceae